ANALISIS YURIDIS KLAUSUL DISCLAIMER OLEH PELAKU USAHA PADA SITUS JUAL BELI ONLINE (E-COMMERCE) - Heni Pratiwi (Faculty of Law, Universitas Lampung, 2020)
Disclaimer or exemption clause is a clause or statement used by business actors to restrict or transfer the liability on the rights and obligations of an agreement and legal action. The inclusion of this disclaimer seems to be a freedom for business actors to freely transfer their liabilities which aims to provide protection for them selves, while consumers are being disadvantaged because they cannot file claims or hold accountability in case a default occurs. Therefore, the ease on transferring these liabilities as outlined in the form of a disclaimer is considered a violation of the principle of freedom of contract. This study is a normative research with approach carried out through library study with materials related to the problems of examination. The data sources consisted of primary and secondary data. The collected data were analyzed qualitatively.The results of the study showed that: a). The status of the disclaimer according to the law of agreement was declared null and void because it did not fulfill the objective conditions contained in Article 1320 of the Civil Code, namely legal reasons, containing provisions that contravened the law and violation of the principle of freedom of association. b). The validity of electronic transactions viewed from Article 1320 of the Civil Code was only valid if it fulfilled the four valid conditions of the agreement, both subjective and objective conditions. If these subjective conditions are not met, then as a legal consequence the e-commerce sale and purchase contract would be canceled, and if the objective conditions are not met, the contract would be made null and void, c). The form of legal protection for consumers against the first disclaimer/exemption clause, through preventive protection, UUPK (the Consumers Protection Act) has designed a preventive provision by regulating prohibitions for business actors to include disclaimer clause and it is required to adjust the contents of the disclaimer clause regulated in Chapter V Article 18 of UUPK. Second, through repressive protection which aims to resolve disputes in order to protect consumers. The consumers can resolve the dispute through lawsuit (litigation) and without the intervention of the court (non litigation).